Utilization of Animiz Animation Application in Arabic Class 2 Madrasah Tsanawiyah Lessons at Diniyyah Pasia Modern Islamic Boarding School - Azizul Maryati; Ali Ameer; Jams Egie (Scientechno: Journal of Science and Technology, 2022)
This study uses a qualitative method. With this method, the researcher conducted interviews with some members of the second class of private madrasah tsanawiyyah at the modern Islamic boarding school Diniyyah Pasia, Agam. This Animiz Animation application is one of the animation media-based applications that really helps students to understand the presentation of material explained using moving images which increases the interest and interest of everyone to listen carefully to the explanations in the video and understand and understand the explanations provided. There by looking at the animation created. The benefit of this application is that it makes it easier for educators to convey the subject matter they want to convey and also for students, with this application educators do not need to carry out teaching and learning activities with the conventional system, namely face to face especially during the covid-19 pandemic. With this application, information and communication technology is also developing because if you use this application often, knowledge about this application will be spread and can be increased to a higher and sophisticated level. By conducting this research, it is also hoped that learning media that were previously unknown will become known because of the practicality of understanding using animation media because it has described the purposes of the explanations presented in the video presentations made. Educational technology using advances in information and confirmation will increase if knowledge about it is growing. Then the educational media becomes more sophisticated and practical and makes the education system in Indonesia more developed and advanced.